2020
DOI: 10.1155/2020/8293921
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammation in the Pathogenesis of Osteoarthritis

Abstract: A joint is the point of connection between two bones in our body. Inflammation of the joint leads to several diseases, including osteoarthritis, which is the concern of this review. Osteoarthritis is a common chronic debilitating joint disease mainly affecting the elderly. Several studies showed that inflammation triggered by factors like biomechanical stress is involved in the development of osteoarthritis. This stimulates the release of early-stage inflammatory cytokines like interleukin-1 beta (IL-1β), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
246
0
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(263 citation statements)
references
References 110 publications
(192 reference statements)
4
246
0
13
Order By: Relevance
“…Besides, increased PGE 2 inhibits the proliferation of chondrocytes and reduces the synthesis of ECM [28].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, increased PGE 2 inhibits the proliferation of chondrocytes and reduces the synthesis of ECM [28].…”
Section: Discussionmentioning
confidence: 99%
“…P38 MAPK is one of pathways in MAPK signaling pathway,which regulated the expression of proin ammatory cytokines such as IL-1β and TNF-α to accelerate cartilage degeneration in KOA [32]. When growth factors and pro-in ammatory cytokines bind to corresponding receptors on the cell membrane, the pathway will be triggered.Then p38 will be phosphorylated and in turn active other in ammatory cytokines in downstream [9]. Recently, researchers have reported that synovial in ammantion is another important factor which can aggravate KOA by osteophytosis, cartilage degeneration and in ammation [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while KOA has been classi ed as non-in ammatory disease for a long time, the degree of in ammation is now considered as a critical factor in KOA pathology [8]. Several studies indicated that in the early-stage of KOA, many in ammation cytokines like tumor necrosis factor alpha (TNF-α) and interleukin-1 beta ( IL-1β) ,which triggered by factors such as biomechanical stress ,will active the signaling pathways and then in turn accelerate the progression of KOA [9].…”
Section: Introductionmentioning
confidence: 99%
“…Enrico Ragni 1 , Laura Mangiavini 2,3 , Marco Viganò 1 , Anna Teresa Brini 4,5 , Giuseppe Michele Peretti 2,3 , Giuseppe Banfi 2,6 and Laura de Girolamo 1, *…”
Section: Management Of Osteoarthritis During the Covid-19 Pandemicunclassified
“…Among cytokines, the most studied are interleukin 1 β (IL-1β) and tumor necrosis factor α (TNF-α), which can activate cartilage matrix degeneration by activation of toll-like receptors (TLRs). 5 Moreover, IL-15 and IL-17 are also secreted by the synovium lymphocytes and are associated with OA progression by inducing chemokine production by synovium fibroblast and chondrocytes. 5 In articular cartilage, the degenerative process is initiated by biomechanical stress and inflammation.…”
Section: Aim Of the Reviewmentioning
confidence: 99%